Analisis Komparatif antara Probability dan Nonprobability dalam Penelitian Pemasaran - Khaidir Ali Fachreza; Mukhlis Harvian; Nasya Zahra; Muhammad Izzudin Islam; Muhammad Daffa; Miftahul Chair; Mia Lasmi Wardiyah (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
Marketing research plays a crucial role in the context of modern business today. To achieve the desired level of accuracy and benefit, it is vital to conduct this research using the appropriate method. Within the scope of marketing research, there is a significant debate between the use of probability and nonprobability methods. Each method has different strengths and weaknesses in producing quality research data. Therefore, it is essential to perform a comprehensive analysis to understand the benefits and consequences offered by both approaches. From this analysis, a better understanding of the most suitable method choice for each situation and marketing research need will be generated. By using the right method, researchers can maintain the level of validity and reliability of the data obtained. This step is crucial to ensure that the results of marketing research can serve as an accurate and useful guide for business decision-making.